Rethinking language, text and context: interdisciplinary research in stylistics in honour of Michael Toolan - Page, Ruth E.; Busse, Beatrix; Nørgaard, Nina (Routledge studies in rhetoric and stylistics, 2020)
This collection of original research highlights the legacy of Michael Toolan's pioneering contributions to the field of stylistics and in so doing provides a critical overview of the ways in which language, text, and context are analyzed in the field and its related disciplines. Featuring work from an international range of contributors, the book illustrates how the field of stylistics has evolved in the 25 years since the publication of Toolan's seminal Language, Text and Context, which laid the foundation for the analysis of the language and style in literary texts. The volume demonstrates how technological innovations and the development of new interdisciplinary methodologies, including those from corpus, cognitive, and multimodal stylistics, point to the greater degree of interplay between language, text, and context exemplified in current research and how this dynamic relationship can be understood by featuring examples from a variety of texts and media. Underscoring the significance of Michael Toolan's extensive work in the field in the evolution of literary linguistic research, this volume is key reading for students and researchers in stylistics, discourse studies, corpus linguistics, and interdisciplinary literary studies"--